N‐glycome analysis detects dysglycosylation missed by conventional methods in SLC39A8 deficiency. Issue 6 (14th September 2020) - Park, Julien H.; Mealer, Robert G.; Elias, Abdallah F.; Hoffmann, Susanne; Grüneberg, Marianne; Biskup, Saskia; Fobker, Manfred; Haven, Jaclyn; Mangels, Ute; Reunert, Janine; Rust, Stephan; Schoof, Jonathan; et al.
Abstract: Congenital disorders of glycosylation (CDG) are a growing group of inborn metabolic disorders with multiorgan presentation. SLC39A8‐CDG is a severe subtype caused by biallelic mutations in the manganese transporter SLC39A8, reducing levels of this essential cofactor for many enzymes including glycosyltransferases. The current diagnostic standard for disorders of N ‐glycosylation is the analysis of serum transferrin. Exome and Sanger sequencing were performed in two patients with severe neurodevelopmental phenotypes suggestive of CDG. Transferrin glycosylation was analyzed by high‐performance liquid chromatography (HPLC) and isoelectric focusing in addition to comprehensive N ‐glycome analysis using matrix‐assisted laser desorption ionization time of flight (MALDI‐TOF) mass spectrometry (MS). Atomic absorption spectroscopy was used to quantify whole blood manganese levels. Both patients presented with a severe, multisystem disorder, and a complex neurological phenotype. Magnetic resonance imaging (MRI) revealed a Leigh‐like syndrome with bilateral T2 hyperintensities of the basal ganglia. In patient 1, exome sequencing identified the previously undescribed homozygous variant c.608T>C [p.F203S] in SLC39A8 . Patient 2 was found to be homozygous for c.112G>C [p.G38R]. Both individuals showed a reduction of whole blood manganese, though transferrin glycosylation was normal. N ‐glycome using MALDI‐TOF MS identified an increase of the asialo‐agalactosylated precursor N ‐glycan A2G1S1 and a decrease in bisected structures. In addition, analysis of heterozygous CDG‐allele carriers identified similar but less severe glycosylation changes. Despite its reliance as a clinical gold standard, analysis of transferrin glycosylation cannot be categorically used to rule out SLC39A8‐CDG. These results emphasize that SLC39A8‐CDG presents as a spectrum of dysregulated glycosylation, and MS is an important tool for identifying deficiencies not detected by conventional methods. Abstract :